2012
DOI: 10.3111/13696998.2011.653512
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness achieved through changing the composition of renal replacement therapy in Japan

Abstract: Appropriate distribution of all transplant options and hemodialysis is necessary to achieve the most cost-effective solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The study population of all studies were patients with ESKD, but only four studies described characteristics of the base case population [20,24,27,29]. Five of the ten studies conducted a CUA [20][21][22][23][24], one conducted a CEA [25], and four conducted both a CEA and CUA [26][27][28][29]. Eight studies were model-based economic evaluations using Markov models [20][21][22][23][26][27][28][29] and the remaining two studies were a multicenter cross-section study [24] and a retrospective cohort study [25], respectively.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study population of all studies were patients with ESKD, but only four studies described characteristics of the base case population [20,24,27,29]. Five of the ten studies conducted a CUA [20][21][22][23][24], one conducted a CEA [25], and four conducted both a CEA and CUA [26][27][28][29]. Eight studies were model-based economic evaluations using Markov models [20][21][22][23][26][27][28][29] and the remaining two studies were a multicenter cross-section study [24] and a retrospective cohort study [25], respectively.…”
Section: Study Selectionmentioning
confidence: 99%
“…Five of the ten studies conducted a CUA [20][21][22][23][24], one conducted a CEA [25], and four conducted both a CEA and CUA [26][27][28][29]. Eight studies were model-based economic evaluations using Markov models [20][21][22][23][26][27][28][29] and the remaining two studies were a multicenter cross-section study [24] and a retrospective cohort study [25], respectively. Four studies were conducted from a public healthcare perspective [21,22,24,27], three from a societal perspective [20,23,29] and three from a third-party payer perspective [25,26,28].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Costs of maintaining a functioning kidney graft in high-income countries range from approximately U.S. $10,000 to $20,000 per person per year: by comparison, costs of in-center hemodialysis range from approximately U.S. $50,000 to $90,000 per person per year. [8][9][10][11] Given that kidney transplantation is also associated with a substantial increase in life years compared to remaining on the waiting list, 12 as well as significant gains in quality of life, 13 maximizing the rate of transplantation is considered an economically dominant strategy for health systems in high-income countries, and this is typically reflected in health policies with respect to organ donation and transplantation. Economic evaluations conducted in upper-to middle-income countries have demonstrated that transplanting a greater proportion of dialysis patients in this setting would similarly result in cost savings from the perspective of a single payer and an increase in life years gained.…”
mentioning
confidence: 99%